2017
DOI: 10.1038/s41598-017-00582-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Gyrification Trajectories of Human Brain in Healthy Individuals and Patients with Major Psychiatric Disorders

Abstract: Cortical gyrification of the brain represents the folding characteristic of the cerebral cortex. How the brain cortical gyrification changes from childhood to old age in healthy human subjects is still unclear. Additionally, studies have shown regional gyrification alterations in patients with major psychiatric disorders, such as major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SCZ). However, whether the lifespan trajectory of gyrification over the brain is altered in patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 68 publications
8
95
1
Order By: Relevance
“…Regarding the changes of LGI, we found it correlated with age in negative effect in multiple brain regions, which were also observed in previous studies . Hogstrom et al found that LGI significantly decreased in the postcentral, supramarginal, and inferior parietal lobes, the same as our results; while they did not find an obvious decline in rostral anterior cingulate which was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the changes of LGI, we found it correlated with age in negative effect in multiple brain regions, which were also observed in previous studies . Hogstrom et al found that LGI significantly decreased in the postcentral, supramarginal, and inferior parietal lobes, the same as our results; while they did not find an obvious decline in rostral anterior cingulate which was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In another report, the average local gyrification trajectory followed a logarithmic function with age from 4 to 83 years. 28 Due to lack of the subjects aged 4-20, we did not find a logarithmic relationship and studies are required in the future for the development.…”
Section: Discussionmentioning
confidence: 82%
“…Using a whole brain approach, we found the strongest gyrification reduction in the very preterm sample bilaterally in the insula, a deeply buried region characterized by elevated convolution complexity across lifespan (12,64). The insula, the first lobe to differentiate in fetal life, starts sulcation/gyrification at 16 weeks of gestation (4,65) and undergoes critical development between 21 and 32 weeks (66), making it particularly vulnerable to alterations following very preterm birth.…”
Section: Discussionmentioning
confidence: 98%
“…Already, signs of this paradigm shift are appearing. There is a small, but important, body of research that is developing sophisticated models of the trajectories of different facets of brain ageing, using a range of neuroimaging modalities . These models, often using longitudinal data, have the potential to map out an individual's future brain health.…”
Section: Focusing On Commonalities Could Lead To a Paradigm Shiftmentioning
confidence: 99%